Hormone replacement therapy alone or in combination with tamoxifen in women with thin endometrium undergoing frozen-thawed embryo transfer: A retrospective study - Shi, Qingqing; Huang, Chenyang; Liu, Jingyu; Li, Yifan; Kong, Na; Mei, Jie; Shen, Xiaoyue; Sun, Yanxin; Lu, Feifei; Sun, Haixiang; Yan, Guijun (Frontiers in Endocrinology, 2023)
Research question: To investigate the effects of two protocols (hormone replacement therapy (HRT) alone or in combination with tamoxifen) on the endometrium and pregnancy outcome of patients with thin endometrium in frozen-thawed embryo transfer (FET) cycles. Design: A total of 465 infertile patients with thin endometrium who underwent FET between January 2020 to June 2021 at the Drum Tower Hospital affiliated with Nanjing University Medical School were retrospectively analyzed. A total of 187 patients were given tamoxifen in addition to HRT (TMXF-HRT group), whereas 278 patients were given only HRT (HRT group). Clinical data were compared between the two groups, including general characteristics, endometrial thickness, and clinical pregnancy outcomes. Results: There were no significant differences in baseline characteristics of all enrolled patients between two groups. Serum progesterone (P) was higher in HRT group than in the TMXF-HRT group (0.28 ± 0.53 ng/mL vs. 0.15 ± 0.25 ng/mL, P = 0.002). There was a significant increase in endometrial thickness in the TMXF-HRT group compared with the HRT group (OR: 1.54, 95% CI: 1.32-1.75, P < 0.001). There were no significant differences in the clinical pregnancy rate, embryo implantation rate, early miscarriage rate, or live birth rate between these two groups. Conclusion: Although tamoxifen when used in combination with hormone replacement therapy can significantly increase endometrial thickness, it may not have a role in improving the pregnancy outcomes of patients with thin endometrium undergoing FET cycles.